Advanced epithelial ovarian cancer – studies on preoperative [18F] FDG PET/CT and HE4 profile during primary chemotherapy - Hynninen, Johanna (Annales Universitatis Turkuensis D 1154, 2015)
Epithelial ovarian cancer (EOC) is usually diagnosed in an advanced stage. The prognosis depends highly on the amount of the residual tumor in surgery. In patients with extensive disease, neoadjuvant chemotherapy (NACT) is used to diminish the tumor load before debulking surgery. New non-invasive methods are needed to preoperatively evaluate the disease dissemination and operability. [18F] FDG PET/CT (Positron emission tomography/computed tomography) is a promising method for cancer diagnostics and staging. The biomarker profiles during treatment can predict patient’s outcome. This prospective study included 41 EOC patients, 21 treated with primary surgery and 20 with NACT and interval surgery. The performances of preoperative contrast enhanced PET/CT (PET/ceCT) and diagnostic CT (ceCT) were compared. Perioperative visual estimation of tumor spread was studied in primary and interval surgery. The profile of the serum marker HE4 (Human epididymis 4) during primary chemotherapy was evaluated. In primary surgery, surgical findings were found to form an adequate reference standard for imaging studies. After NACT, the sensitivity for visual estimation of cancer dissemination was significantly worse. Preoperative PET/ceCT was more effective than ceCT alone in detecting extra-abdominal disease spread. The high number of supradiaphragmatic lymph node metastases detected by PET/ceCT at the time of diagnosis brings new insight in EOC spread patterns. The sensitivity of both PET/CT and ceCT remained modest in intra-abdominal areas important to operability. The HE4 profile was in concordance with the CA125 profile during primary chemotherapy. Its role in the evaluation of EOC chemotherapy response will be clarified in further studies.